ISOLATION AND CHARACTERIZATION OF β-SITOSTEROL FROM LANTANA CAMARA - Punna Lavanya; Dr.S.Venkata Saibaba, Prathibareddy Nareddy, V.Sandhya, T.Malleshwari (EPRA International Journal of Research and Development (IJRD), 2022)
Objective: The aim of our study was to investigate chemical constituents of leaves and aerial of Lantana camara since not much phytochemical investigation had been done previously in India. Methods: Phytochemical screening of the extracts obtained from the leaves of L.camara indicated the presence of flavonoids (type of flavonols), saponins, alkaloids, steroids, and terpenoids. Thin-layer chromatography fingerprinting and the spraying reagent (concentrated H2SO4 and vanillin in ethanol) were used to identify the hexane extract containing phytosterols. Results: The different chromatographic and spectroscopic results revealed the presence of β‐sitosterol isolated from L.camara. Conclusion: The isolation and purification afforded white crystalline powder which was subjected to chemical and spectral identification by infrared and 1H‐nuclear magnetic resonance. The compound was identified as β‐sitosterol.